Coalitions in Collision : Malaysia's 13th General Elections. - Johan Saravanamuttu, Lee Hock Guan, Mohamed Nawab Mohamed Osman (Institute of Southeast Asian Studies, 2015)
After the watershed 2008 election when the ruling Barisan Nasional (BN) coalition lost its customary two-thirds control of parliamentary seats, there was the not unreasonable expectation that BN would slip even further in the much-anticipated Thirteenth General Election of 2013, which is the subject of this book. In the event, the BN lost the popular vote to the Pakatan Rakyat (PR) but still retained the reins of government. In this book, prominent Malaysian specialists and experts will provide.